DETERMINATION OF FRACTURE TOUGHNESS AND STRAIN ENERGY RELEASE RATE FOR BASALT/EPOXY COMPOSITES - Lal, Chandreshah (IRC, 2020)
The consideration of using natural fibres in composites is an attempt to produce sustainable and cost-friendly materials. This study focuses on determining the fracture toughness and strain energy release rate of basalt fibre and epoxy matrix composites. The determination of fracture behaviour will allow for design optimization of components and the experimental values are useful for numerical analysis. Samples tested are unidirectional plies of the basalt fibre which are in 0˚ and 90˚ fibre orientations. This will provide an in depth understanding on the fracture properties of unidirectional samples if they exhibit intralaminar or translaminar fracture behaviour.